The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1748-1716.2007.01723.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute resistance exercise increases skeletal muscle angiogenic growth factor expression

Abstract: These findings suggest that acute resistance exercise increases skeletal muscle VEGF, VEGF receptor and angiopoietin receptor expression. The increases in muscle angiogenic growth factor expression in response to acute resistance exercise are similar in timing and magnitude with responses to acute aerobic exercise and are consistent with resistance exercise promoting muscle angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 52 publications
10
71
0
4
Order By: Relevance
“…Contrary to the purported mechanisms for exercise-training induced improvements in MBF (which include angiogenesis (Gavin et al 2007), capillarization (McCall et al 1996) and vascular remodelling of the arteriolar network (Weber et al 2013)), independent mechanisms must underlie the results observed in this acute intervention study as the compressed timeframe negates the possibility for the mechanisms outlined above. Based on the wellestablished improvements in endothelium dependent vasodilation afforded by the consumption of cocoa flavanols, possible mechanisms for this include altered: metabolite profiles (Schroeter et al 2006), cell signaling pathways, gene expression and/ or protein activity (Middleton et al 2000;Scalbert et al 2005), although our results suggest that this improvement is not linked to insulin signaling pathways as there were no differences in plasma insulin, proximal insulin signaling (AKT) or dextrose requirement to maintain a fixed blood glucose between the groups.…”
Section: Discussionmentioning
confidence: 89%
“…Contrary to the purported mechanisms for exercise-training induced improvements in MBF (which include angiogenesis (Gavin et al 2007), capillarization (McCall et al 1996) and vascular remodelling of the arteriolar network (Weber et al 2013)), independent mechanisms must underlie the results observed in this acute intervention study as the compressed timeframe negates the possibility for the mechanisms outlined above. Based on the wellestablished improvements in endothelium dependent vasodilation afforded by the consumption of cocoa flavanols, possible mechanisms for this include altered: metabolite profiles (Schroeter et al 2006), cell signaling pathways, gene expression and/ or protein activity (Middleton et al 2000;Scalbert et al 2005), although our results suggest that this improvement is not linked to insulin signaling pathways as there were no differences in plasma insulin, proximal insulin signaling (AKT) or dextrose requirement to maintain a fixed blood glucose between the groups.…”
Section: Discussionmentioning
confidence: 89%
“…6,16,54 This finding provides support for the use of resistance training in COPD patients, who display decreased muscle capillarity. 26 Specifically, research has shown that vascular endothelial pg108-113.indd 111 1/11/08 11:11:22 AM growth factor (VEGF) mRNA is increased 2.9-fold above rest 24 hours after resistance exercise in young and aged men as determined by pooled mRNA microarray analysis.…”
Section: Resistance Training and Molecular Adaptations In Skeletal Mumentioning
confidence: 52%
“…The authors concluded that early angiogenic signalling for VEGF is increased by acute resistance exercise although additional research is required to determine the signal transduction pathways responsible for up-regulating the angiogenesis growth factors and receptors. 16 It remains to be determined whether the increased skeletal muscle angiogenesis/capillarity induced by resistance training in healthy young individuals also occurs in COPD patients, who are typically older. In addition, research is also required to determine whether resistance training induced increases in skeletal muscle angiogenesis/ capillarity has any beneficial effect on the functional capacity and HRQL of COPD patients.…”
Section: Resistance Training and Molecular Adaptations In Skeletal Mumentioning
confidence: 99%
“…Diving ability is enhanced by cardiovascular adjustments such as bradycardia (lower heart rate) and peripheral vasoconstriction (Vázquez-Medina et al 2012), while angiogenesis contributes to the maximal oxygen consumption in skeletal muscle capillarity (Gavin et al 2007). Thus, the HIF-1α-induced VEGF expression may contribute to the adaptation of diving species to either aerobic or anaerobic metabolism during breath-hold diving.…”
Section: Discussionmentioning
confidence: 99%